Targeted hypoglossal nerve stimulation for the treatment of obstructive sleep apnea: Six-month results - Friedman, Michael; Bergler, Wolfgang; Maurer, Joachim T. (The laryngoscope, 2016)
Objectives/Hypothesis This feasibility study was designed to show the preliminary safety and efficacy of targeted hypoglossal neurostimulation (THN), and to identify baseline predictors of successful therapy. Study Design Open-label, prospective, multicenter, single-arm cohort study, conducted at seven centers in the U.S.A. and Europe. Methods Forty-six participants with moderate to severe obstructive sleep apnea (OSA), failing or intolerant of continuous positive airway pressure, were implanted. Primary (Apnea-Hypopnea Index [AHI], Oxygen Desaturation Index [ODI]) and secondary (Arousal Index, Epworth Sleepiness Scale Index, Sleep Apnea Quality of Life Index) outcomes were measured at baseline and compared at 6 months. Data were analyzed to identify participant characteristics that would predict success with therapy. Results Sixty-seven adverse events (AEs) were observed among 36 participants; most of the AEs were related to the implant procedure and resolved without sequelae; one device replacement was necessary. Forty-three participants showed significant (P < .01) decreases in both AHI and ODI at 6 months; 35% (15 of 43) met criteria for AHI responders and 40% (17 of 43) for ODI responders. Significant improvement was observed in all the secondary endpoints. Predictors-of-success selection criteria were identified as baseline AHI < 65/hr, baseline apnea index ≤ 30, baseline body mass index < 35, and <15 events/hr of SpO2 decrease > 10%. Seven participants met these criteria; 86% (6 of 7) were AHI responders and 86% (6 of 7) were ODI responders, indicating that THN therapy can be efficacious in a carefully selected population of OSA patients. Conclusions This feasibility study suggests that THN therapy is likely to be safe and effective in selected patients. Level of Evidence 2b Laryngoscope, 126:2618-2623, 2016
Gesehen am 31.10.2019